(untitled) (Research, Society and Development, 2020)
The objective of this article is to relate how to experience monitoring in the discipline Health Management and Nursing I, with a view to semi-presential education. It´s about a descriptive study, the type of experience report, carried out from the experience of students in the monitoring of a semipresential subject. The monitoring experience was an initiation to teaching, in which the monitor came to know the activities inherent to teaching practice, under guidance. Being a monitor in a semi-presential discipline provided a more detailed knowledge of this modality, which provides flexibility in the learning process, encouraging the development of new digital skills, such as autonomy, self-motivation, critical reflection, analysis and decision-making skills. in the face of problem situations, teamwork, the use of different languages and collaborative action. It is concluded that the experience of monitoring contributed both to the academic training of the monitor, as well as to the progress of the semi-presential discipline, favoring communication and the development of virtual and face-to-face activities.